Power endurance changes in alpine ski racing - Patterson, C.; Platzer, H.-P.; Raschner, C. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Bosco (1997) developed a power endurance test for ski racers, suggesting that speed endurance measured with jumps is the most important physical capacity for skiers. The question of how to train for power endurance has been often raised. One opinion is that higher maximal strength and power in the weight room will improve power endurance on the ski hill. In the summer of 2010 coaches focused more on maximum strength and power training. The aim of this study was to examine and compare the relative power and power endurance capacities of Austrian female ski racers in 2010 to 2008 and 2009.